Perempuan dan Teknologi Informasi - Faiz, Fahruddin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
The patriarchal culture that is gender biased has been proven to bring a negative effect in the harmony of human life. Men and women ideally must complete one-another and support each other in different ways. However patriarchal culture has made men became the main actors, dominant and hegemonic, and women became the figurant side, on the border and unable to express themselves. This 'sidedness' in the world of informational technology is one of the real facts in this problem. This article tries to prove how women's access to the technological world has been 'walled' since the beginning and how women are positioned only as a profitable object by exploiting their body and sexuality by technological practitioners. In the end of this article, the writer advises the need of a world-view patriarchal deconstruction, a cultural revolution, and a reformation of social structure as a way out of this problem.